PRELIMINARY SCREENING OF PHYTOCHEMICAL COMPONENTS OF PARTHENIUM HYSTEROPHORUS LEAVES AND STUDY OF AUTOTOXIC POTENTIAL OF PARTHENIUM ON ITS MORPHOLOGICAL PARAMETERS - Kapoor, Riti Thapar (LIFE: International Journal of Health and Life-Sciences, 2016)
The pot studies were conducted to determine the auto toxic potential of Parthenium hysterophorus leaves on its own morphological parameters. The leaves of Parthenium weed contain several phytochemical components such as phenol compounds, terpenoids and steroids etc. Auto toxicity is a process where a plant or its decomposing residues release toxic chemicals into the environment which may inhibit germination and growth of the same plants. Auto toxicity is closely related to the soil sickness. In the present study the morphological parameters of Parthenium weed such as number of seedlings, number of leaves/plant, plant height, branches/plant, capitula and seeds/plant were significantly inhibited by leaf powder of Parthenium hysterophorus. The reduction in morphological parameters was in the order: T2 treatment > T1treatment > Control. Hence, the auto toxic potential of Parthenium hysterophorus can be utilized as eco-friendly strategy for weed control.